The Role of Guided Inquiry to Improve Critical Thinking Skills in Physics Education: A Systematic Review of Indonesian Studies - Yaumie, Savana Nisva; Jatmiko, Budi; Satriawan, Muhammad; Supardi, Zainul Arifin Imam; Arivi, Maharani Agustina (FKIP Universitas Lampung, 2025)
This study aims to systematically analyze the role of the Guided Inquiry model in improving students' critical thinking skills in physics education in Indonesia, while also identifying current research trends, implementation strategies, and gaps in the literature. The study employed a systematic literature review (SLR) using the PRISMA framework, complemented by a bibliometric analysis, to substantiate the results. Articles were retrieved from the SINTA, DOAJ, and Google Scholar databases with a publication period from 2018 to early 2025 using the Boolean string (“inkuiri terbimbing” OR “guided inquiry”) AND (“berpikir kritis” OR “critical thinking” OR “higher-order thinking skills”). Of the 117 articles identified, 27 met the inclusion criteria and were further analyzed. The analysis was descriptive, based on the year of publication, research design, educational level, instruments, and data analysis methods, as well as bibliometric mapping using VOSviewer to identify research clusters and emerging gaps. The results of the study show that the guided inquiry model is most commonly used at the upper secondary level, often employing quasi-experimental research designs, particularly pre-test-post-test control groups, and data analysis methods such as t-tests and N-gain. The dominant instrument is the essay test, although it has the disadvantage of subjectivity in assessment. The bibliometric visualization reveals that keywords such as critical thinking, guided inquiry model, and data analysis are the focus of research, while the aspect of practical applicability remains relatively underinvestigated. Another interesting finding is that the assessment indicators show the highest increase, as guided inquiry encourages students to compare the experiment results with the theoretical framework. In contrast, the self-regulation indicators show the lowest increase, which is attributed to a lack of reflective exercises and the limitations of the assessment tools. Overall, guided inquiry has proven effective in promoting various dimensions of critical thinking, especially in physics topics that require logical thinking and data analysis. However, the aspect of self-reflection is not yet sufficiently addressed and requires more attention in lesson design and assessment strategies. This study contributes to the field by providing a systematic and bibliometric mapping of the relevant literature, which can serve as a reference for teachers, researchers, and policymakers in designing more innovative, context-based physics lessons focused on strengthening 21st-century skills. Keywords: guided inquiry, critical thinking skills, physics learning.